HEALTH SEEKING BEHAVIOR DI KALANGAN MASYARAKAT URBAN DI KOTA YOGYAKARTA - Aris Widayati (Sanata Dharma University, 2012)
Abstract : Research presented in this article investigated health seeking behavior among peoplein an urban area of Yogyakarta City Indonesia. The research was a cross-sectional surveyinvolved adults in Yogyakarta City who were selected using a cluster random samplingtechnique. Sample size was 640 respondents. Data were collected using a pre-testedquestionnaire during March to May 2010. Data were analyzed using descriptive statistics, Chisquare tests, and Logistic regression. A total of 559 questionnaires were completed, resulted in90% of response rate. Mostly respondents stated that they had one to three medical complaintswithin a month (51% of 559). The most popular health seeking behavioris a combination betweenself-care and consultation to health care providers (41%). Other options are self-care (36%),consultation to public health care centre (16%), and consultation to private health care (5%).Among the socio-demographic and economic characteristics, marital status is the only factorthat significantly correlated with health seeking behavior. Based on the results it can berecommended that programs for improving health behavior should consider self-care, includingno medication and self medication with modern and herbal/traditional medicines. The role offamily members (e.g. spouse) should also be considered as an important factor of health relatedbehavior.Keywords : Health seeking behavior